Research on adsorptive desulfurization of HS from natural gas over MnO-CoO supported on activated carbon - Jiao J Zhang; Li P Shen; Hua Song; Lu Wang; Xue Q Wang; Ling Dong (Adsorption Science & Technology)
Mn x O y , Co x O y , and Mn x O y -Co x O y supported on activated carbon (AC) adsorbents have been successfully prepared and characterized by specific surface area (BET), X-ray photoelectron spectroscopy, X-ray diffraction analysis, and Fourier-transform infrared spectroscopy. The results show that Mn is present in the form of Mn 3+ and Mn 4+ , and Co is present in the form of Co 2+ and Co 3+ . For all of the modified samples, the functional groups of the AC were well retained and the specific surface areas followed the order: AC > Mn x O y -Co x O y /AC > Co 3 O 4 /AC > Mn x O y /AC. For Mn x O y -Co x O y /AC, Mn and Co mainly exist in the forms of MnO 2 , Co 3 O 4 , and Mn 3 Co 2 O 8 . Mn x O y -Co x O y /AC was found to exhibit the best H 2 S desulfurization performance. At 20℃, the breakthrough time and saturated adsorption time were 115 min and 185 min, and the saturated sulfur capacity and desulfurization rate were 347.7 mg/g and 74.2%. The H 2 S removal capacities of the different adsorbents decreased in the order: Mn x O y -Co x O y /AC > Mn x O y /AC > Co x O y /AC > AC.